1996
DOI: 10.1073/pnas.93.17.9090
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester is a potent and specific inhibitor of activation of nuclear transcription factor NF-kappa B.

Abstract: Caffeic acid phenethyl ester (CAPE), an active component of propolis from honeybee hives, is known to have antimitogenic, anticarcinogenic, antiinflammatory, and immunomodulatory properties. The molecular basis for these diverse properties is not known. Since the role of the nuclear factor NF-cB in these responses has been documented, we examined the effect of CAPE on this transcription factor. Our results show that the activation of NF-KcB by tumor necrosis factor (TNF) is completely blocked by CAPE in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
810
1
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,046 publications
(865 citation statements)
references
References 37 publications
(48 reference statements)
49
810
1
5
Order By: Relevance
“…Caffeic acid phenethyl ester (CAPE) has been shown to inhibit translocation of NF-kB. 31 To confirm the efficacy of CAPE in our system, we showed that pre-treatment of 253J cells with CAPE alone or with a combination of CAPE and TRAIL abrogated translocation of the p50 and p65 nuclear factor (NF)-kB subunits to the nucleus (Supplementary Figure 2). SB202190 specifically inhibits the activity of p38 MAPK by competing for the ATP-binding sites of the a and b isoforms.…”
Section: The Role Of Nf-jb and P38 Mapk Pathways In Trail-induced Apomentioning
confidence: 73%
“…Caffeic acid phenethyl ester (CAPE) has been shown to inhibit translocation of NF-kB. 31 To confirm the efficacy of CAPE in our system, we showed that pre-treatment of 253J cells with CAPE alone or with a combination of CAPE and TRAIL abrogated translocation of the p50 and p65 nuclear factor (NF)-kB subunits to the nucleus (Supplementary Figure 2). SB202190 specifically inhibits the activity of p38 MAPK by competing for the ATP-binding sites of the a and b isoforms.…”
Section: The Role Of Nf-jb and P38 Mapk Pathways In Trail-induced Apomentioning
confidence: 73%
“…We show here that, indeed, NF-kB p65/p50 overexpression leads to MMP-13 promoter transactivation and that CSE suppresses the p65/p50-driven MMP-13 promoter activation, thereby suggesting that CSE's MMP-inhibitory actions are related to its blockade of the NF-kB signaling. Furthermore, the comparison to CAPE, a chemically defined specific inhibitor of NF-kB (Natarajan et al 1996), revealed that CSE was only about 4 times less active in our assay. Our results go along with previous reports demonstrating that CSE and its constituents interfere with NF-kB signaling in different cell types.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, inhibitors of mitochondrial electron transport that suppress ROI production (like rotenone) or overexpression of antioxidizing enzymes, such as MnSOD and catalase, can block TNFa-induced activation of NF-kB (Schulze-Osthoff et al, 1993;Manna et al, 1998Manna et al, , 1999. Caffeic acid phenethyl ester, a phenolic antioxidant and a structural relative of flavonoids, may directly interfere with DNA binding by NF-kB (Natarajan et al, 1996), and this effect on DNA binding can be reversed by reducing agents like dithiothreitol . Therefore, all antioxidants probably do not act at the same level to inhibit NF-kB.…”
Section: Antioxidantsmentioning
confidence: 99%